(untitled) (Research, Society and Development, 2020)
It analyzes the role of writing practices in the continuing education of teachers working in early childhood education in the city of Vitória/ES. It is a collaborative research-action, which uses as a source 30 textual productions, elaborated by Physical Education, Arts and Classroom Teachers (Pedagogy) participating in a continuing education course. The tematic analysis, used to interpret the data, allows to group textual productions into three categories: writing as a teaching exercise (40.6%); forms of writing (bureaucratic and reflective) (33.4%); and writing as a formative option (26%). It is concluded that the continuing education, promoted in the articulation between university and school, contributed to the development of a qualified writing, able of enhancing the reflection / reframing of the pedagogical practice and the production of knowledge by the teachers.